Short term toxicity of nanomaterials in different development stages of amphibians - Costa, Nuno Mouta Faria da (2014)
The production of engineered nanomaterials is rising and constantly growing. The fast advances in this industry are causing the introduction of nanomaterials (NMs) into the environment, namely into aquatic ecosystems. The specific properties that these new compounds exhibit may promote higher toxicity to biota, comparatively to their bulk counterparts. Size, charge, surface area, aggregation index, among others, may dictate the availability and the degree of toxicity of NMs in aquatic environments, especially when assembled with environmental changing conditions such as pH and temperature. Amphibians are excellent bioindicators to study the risk associated with the release of NM into the aquatic environment, since they inhabit a wide variety of freshwater habitats associated with industrial contamination. The present work intended to study the toxicity of NMs to different life stages of amphibians, concerning the increase of global temperature that is currently taking place. In order to achieve this, two specific goals were determined: i) evaluate the influence of temperature in the toxicity of NMs of hidrophobically modified polyacrylic acid (HM-PAA) to tadpoles of Epidalea calamita and Pelophylax perezi. For this, tadpoles of E. calamita and P. perezi were exposed to a range of six concentrations of HM-PAA plus a control, at 20ºC and 25ºC. Results showed lethal and sublethal toxicity of HM-PAA, but a clear pattern of temperature influence in the toxicity of HM-PAA could not be unveiled; ii) assess the influence of Si-NM size and temperature in the toxicity of this NM to embryos of Pelophylax perezi. To attain this goal, embryos of P. perezi were exposed to a range of six concentrations of three differently sized Si-NMs (SM30-7nm, HS30-12nm, and TM40-22nm) plus a control, at 20ºC and 26ºC. Results obtained show lethal and sublethal toxicity caused by all the Si-NM and an increased toxicity at higher temperatures. Furthermore, it was observed that the NM presenting the lowest primary size exhibited the highest toxicity.